Impacts of two-year multisectoral cash plus programs on young adolescent girls’ education, health and economic outcomes: Adolescent Girls Initiative-Kenya (AGI-K) randomized trial - Karen Austrian; Erica Soler-Hampejsek; Beth Kangwana; Yohannes Dibaba Wado; Benta Abuya; John A. Maluccio (BMC Public Health, 2021)
Abstract Background Early adolescence is a critical window for intervention when it is possible to lay a foundation for a safe transition to adulthood, before negative outcomes occur. The Adolescent Girls Initiative–Kenya randomized trial tested the effects of combinations of interventions for young adolescent girls in two sites – the Kibera informal settlement in Nairobi and rural Wajir County in the Northeastern region. Methods The interventions included community dialogues on the role and value of girls (violence prevention), a conditional cash transfer (education), weekly group meetings for girls with health and life skills training (health), and training and incentives for financial literacy and savings activities (wealth creation). Participants were randomized to one of four study arms: 1) violence prevention only, 2) violence prevention and education, 3) violence prevention, education and health or 4) violence prevention, education, health and wealth creation. An intent-to-treat (ITT) analysis was conducted using longitudinal data to estimate the impact of each combination of interventions and various sensitivity analyses conducted addressing potential attrition bias and multiple hypothesis testing concerns. Results In Kibera, the education conditional cash transfer had small effects on grade attainment but larger impacts on completion of primary school and the transition to secondary school in the most comprehensive arm; the health intervention improved sexual and reproductive health knowledge and condom self-efficacy; and the wealth intervention improved financial literacy and savings behavior. In Wajir, the education conditional cash transfer increased school enrollment and grade attainment, and the wealth intervention improved savings behavior. Conclusions The results indicate that when trying to improve a range of outcomes related to adolescent wellbeing for young girls, a multisectoral intervention with components addressing household economic constraints is a promising approach. Trial registration Trial Registry: ISRCTN, ISRCTN77455458 . Registered 24/12/2015 - Retrospectively registered.